Study of Coefficient of Seepage Irrigation in Tertiary Canals at Village of Kuala Simeme Namorambe District Deli Serdang - Darwana Darwana; Sumono Sumono; Nazif Ichwan (Universitas Sumatera Utara, 2015)
Land water distribution system in the villageof Kuala Simeme is done through tertiary ground channel. Water can loss through evapotranspiration, percolation, and seepage that may affect of the efficiency of water delivery.Of the three factors, the determination of the value of water loss throught seepage in the field was more difficult. This study was aimed to assess the seepage coefficient at two tertiary irrigation canal in the village of Kuala Simeme District of Namorambe, Deli Serdang.The results showed that seepage coefficient in the right edge of the first canal was 3.775,68 mm/day, at the left edge was 10.368,8 mm/day; at the right edge of second canal was 34.368,51 mm/day and at the left edge was 9.562,13 mm/day. Efficiency on first that canal and second canal were 91,02% and 81,73% respectively. Keyword: Tertiary Canal, Efficiency Distribution of water and seepage coefficient